2016
DOI: 10.1177/1039856216632395
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of rehospitalisation in schizophrenia

Abstract: Rehospitalisation rates were higher for patients under the age of 50 and those with shorter index admissions; the latter finding requires further study. Other than the beneficial effect of clozapine, the type and route of prescribed antipsychotics did not significantly affect rehospitalisation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We included 37 studies in the meta‐analysis : three randomised controlled trials and 34 observational studies (Table ). Studies were published between 1990 and 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 37 studies in the meta‐analysis : three randomised controlled trials and 34 observational studies (Table ). Studies were published between 1990 and 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, of the 34 observational studies included in the review, five were considered good quality, 21 were considered moderate quality, and eight were considered poor quality on the Newcastle–Ottawa Scale. Studies were considered poor if they included less than 20 people prescribed clozapine or failed to provide any participant characteristics, for example age, gender distribution, or dose.…”
Section: Resultsmentioning
confidence: 99%
“…Younger age and male gender were the most common factors associated with readmissions to hospitals in nearly all the studies, and across different cultures [e.g. Øiesvold et al (2000) in Norway, Mahendran et al (2005) in Singapore, Woo et al (2006) in USA, Lin et al (2010) and Hung et al (2017) in Taiwan, Dey et al (2016) in New Zealand and Chen et al (2018) in Canada]. Variables that are reflective of social determinants such as, education level, employment and housing were also predictive of rehospitalization (Lay et al 2006;Schmutte et al 2010;van der Post et al 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Recent data on readmission rates among youths showed that more than 30% of young patients are readmitted to acute psychiatric inpatient units within one year after discharge, regardless of their diagnosis of admission [ 18 ]. Regarding psychotic disorders, early readmission can be considered an indicator of psychopathological vulnerability [ 19 ]. A recent meta-analysis focusing on psychiatric readmission of children and adolescents identified suicidal ideation at first admission, prior hospitalization, and discharge from a residential treatment as factors associated with relapse [ 20 ].…”
Section: Introductionmentioning
confidence: 99%